Influência do clima e da fenologia do algodoeiro na dinâmica populacional do pulgão - Araújo, Paulo Afonso Castelo Branco (1985)
The aphid, Aphis gossypii Glover, 1876 (Homopetra: Aphididae), described as a polyphagous and cosmopolitan species which reproduces by thelyotoky is a key insect to cotton plants due its direct action upon the host-plant as well as a virus disease transmitter. [...]